Prevalencia de factores de riesgo cardiovascular en indígenas embera-chamí de Cristianía (Jardín), Antioquia (2015)
ABSTRACT: Prevalence of cardiovascular risk factors was studied in 488 individuals over the age of 14 years in the Karmata Rua indigenous population of Cristianía, Colombia. The following rates were found: arterial hypertension 18.1%, family history of diabetes mellitus 3.3%, serum glucose over 126 mg/dL 0.7%, smoking habit 15%, overweight 40.2%, obesity 8.0%, hypercholesterolemia 21.4%, hypertriglyceridemia 33.3% and dyslipidemia 56.2%. Values of body mass index, total cholesterol, glucose, waist circumference, waist/hip index, systolic and diastolic blood pressure showed a positive and significant correlation with age. Higher level of education showed negative correlation with waist circumference, the waist/hip index, blood sugar and blood pressure. In comparison with other indigenous and non-indigenous communities of Colombia and other countries, prevalence of diabetes mellitus was between three and four times lower in the studied population; prevalence or high blood pressure was also lower despite a tendency to overweight. For other risk factors no significant differences were found, but they were more common in women, in people with low level of schooling and in elder individuals. Probably this difference is caused by genetic and environmental factors, such as increased physical activity in men, diet, and population structure.